Fabrication and enhanced performance of LEDs based on multilayer CdSe@ZnS quantum dot films using layer-by-layer spin-coating with solid-state treatment - Tuan Nguyen, Huu; Tuan Duong, Anh; Lee, Soonil (Chemical Physics, 2023)
We report a novel and facile method to improve the performance of light-emitting devices (LEDs), in which a multilayer colloidal CdSe@ZnS quantum-dots (QDs) was deposited by layer-by-layer spin-coating in combination with 1,2-ethanedithiol (EDT) solid state treatment sequentially to form an emissive layer (EML). The role of EDT treatment is to facilitate the formation of multi-QD layer in LEDs and passivate the surface of QDs, which in turn, modify charge injection properties in QD-LED devices. Based on single carrier device structures, we found that the current density of electron only device decreases while that of hole only device increases significantly upon EDT treatment. The best performance was obtained from the device having a double-QD layers with the maximum luminous yield of 3.64 cd/A, which improved up to 23 times compared to a control device based on a single-QD layer without EDT treatment.
Keywords: EDT treatment; Enhanced performance; multi-QD layers; quantum-dot LED; Spin-coating